Politik Hukum Batas Minimum Usia Perkawinan Pasca Putusan Mahkamah Konstitusi Nomor 22/PUU-XV/2017 - Sania, Yori; Simabura, Charles; Andriani, Henny (Lareh Law Review, 2024)
Abstract Regulations regarding the minimum age for marriage in Indonesia have basically gone through a long history and dynamics starting from the pre-Dutch Colonial government until the New Order era when Law Number 1 of 1974 concerning Marriage was born and was most recently revised into Law Number 16 of 2019 concerning Amendments. Based on Law Number 1 of 1974 concerning Marriage. This research discusses two problem formulations, First, how is the minimum age limit for marriage regulated before the Constitutional Court Decision Number 22/PUU-XV/2017?, Second, what are the legal politics of the minimum age limit for marriage after the Constitutional Court Decision Number 22/PUU-XV/2017 ? To be able to discuss this problem, a normative juridical research method with a historical and statutory approach is used, where the data source used is a secondary data source. From the research and discussions that have been carried out, the following results were obtained: First, the history of setting the minimum age limit for marriage in Indonesia has started since pre-Dutch Colonial times where at that time the applicable marriage law was the respective religious law which was then enforced during the Dutch occupation. Classification is based on ethnicity and each group has its own rules. In the old order era, Law Number 22 of 1946 concerning Marriage Registration, Divorce and Reconciliation (hereinafter referred to as NTR) was born, in the new order era Law Number 1 of 1974 concerning Marriage was born, which was followed by its first revision in the reform era to become Law. Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. Second, the will (political will) of the state authorities is a determining factor in where the law will be directed, including in the issue of determining the minimum age limit for marriage. This can be seen from the development of marriage law in Indonesia starting from the Dutch colonial period, the post-independence period, and the New Order period where marriage law experienced a very strong influence from the interests of the authorities.